Adaptation and Diffusion of Technological Innovations in the Kesepuhan Ciptagelar Indigenous Community of West Java - Rahmat Hidayat, Agus; Utari, Prahastiwi (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research examines the adaptation and diffusion of technological innovation in the Kesepuhan Ciptagelar Indigenous Community. This study aims to determine the diffusion process of technological innovation and the role of Kesepuhan in Ciptagelar in encouraging the application of technology by the needs and customary norms there. The descriptive qualitative method was used to describe the process of innovation diffusion in the application and development of technology in Cipta Gelar Kesepuhan. M. Rogers' innovation diffusion theory is the basis of analysis in this research which has four main elements in the innovation diffusion process: innovation, communication channels, time, and social systems. The research results show that the Ciptagelar Kesepuhan has considered the four main elements of innovation diffusion in encouraging technological adaptation and development. The Ciptagelar Kesepuhan uses a strategy that maximizes the use of the opinion of the leader, namely the Chief Adat, who is assisted hierarchically by the leadership structure there. Community media (CIGA TV and Radio Swarsa Cipta Gelar) and grand deliberations in Ciptagelar are also used as interpersonal communication utilized for communication channels. Those messages are also processed by considering the characteristics of an innovation. The obstacles in adapting innovations or technology depend on the need for benefits and compatibility with customary norms as the basis for applying technology in Kesepuhan Ciptagelar.